Shaping Ability of TRUShape and XP-endo Shaper in C-Shaped Canals Using 3D-Printed Replicas: A Micro-CT Study - Falcão, Natália Pereira da Silva; Marceliano-Alves, Marilia Fagury; Tavares, Sandro Junio Oliveira; Amoroso-Silva, Pablo; Neves, Aline de Almeida; Bastos, Luan Ferreira; Lopes, Ricardo Tadeu; Dantas, Wania Christina Figueiredo; Galhardi, Michelle Paiva Weydt; Marceliano, Eduardo Fagury Videira; Gomes, Cinthya Cristina (European Journal of Dentistry, 2023)
Objective This study compared the shaping ability of TRUShape and XP-endo Shaper systems on C-shaped root canals replicas using microcomputed tomography (micro-CT).Material and Methods Thirty three-dimensional replicas based on a mandibular second molar classified as C1 type I C-shaped canal were randomly divided into two groups (n = 15): TRUShape (G.TRU) and XP-endo Shaper (G.XP) and instrumented with each system according to the manufacturer's instructions. Changes in volume and surface and the unprepared area of the root canal were measured by scanning on micro-CT before and after instrumentation.Results The unprepared areas were 39% in the G.TRU and 43% in the G.XP group with no significant difference between them (p > 0.05), but both the tested systems left a high percentage of unprepared root canal walls of C-shaped root canals.Conclusion TRUShape and XP-endo Shaper showed a high rate of unprepared areas with similar results after C-shaped root canals replicas for root canal preparation.
Keywords: dental materials; X-ray microtomography; root canal preparation; TRUShape; XP-endo Shaper